2016
DOI: 10.1111/ele.12562
|View full text |Cite
|
Sign up to set email alerts
|

Invasive plants have different effects on trophic structure of green and brown food webs in terrestrial ecosystems: a meta‐analysis

Abstract: Although invasive plants are a major source of terrestrial ecosystem degradation worldwide, it remains unclear which trophic levels above the base of the food web are most vulnerable to plant invasions. We performed a meta-analysis of 38 independent studies from 32 papers to examine how invasive plants alter major groupings of primary and secondary consumers in three globally distributed ecosystems: wetlands, woodlands and grasslands. Within each ecosystem we examined if green (grazing) food webs are more sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(74 citation statements)
references
References 79 publications
5
66
1
2
Order By: Relevance
“…Interestingly, we found no evidence that invasive plant impacts on exotic or native animals varied based on trophic level. In contrast, McCary et al () found that invasive plants differentially impacted “green” (e.g., herbivores) and “brown” (e.g., detritivores) food webs. They found that invasive plants decreased primary consumer abundance and increased secondary consumers.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Interestingly, we found no evidence that invasive plant impacts on exotic or native animals varied based on trophic level. In contrast, McCary et al () found that invasive plants differentially impacted “green” (e.g., herbivores) and “brown” (e.g., detritivores) food webs. They found that invasive plants decreased primary consumer abundance and increased secondary consumers.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have found differences in invasive plant impacts across ecosystems (e.g., McCary et al, ; Schirmel et al, ); unfortunately, we lacked adequate replication to test for variation among ecosystems. However, we did have studies spanning seven ecosystem types across the globe, which we grouped into “wet” and “dry.” We found that resident animal abundance was reduced by invasive plants in “wet” ecosystems, with no change in abundance in “dry” ecosystems; though there was no evidence that this impact was different for native and exotic animals.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This lower sensitivity of the higher trophic groups to plant invasion has previously been documented by McCary et al . () who examined the overall effects of invasive plants on aboveground food web in wetlands. Basal detritus resources can affect predators in the food web through altering the food source via the bottom‐up cascading effect (Pace et al .…”
Section: Discussionmentioning
confidence: 99%
“…Further, invasive plants that have much higher litter quality than native species can greatly enhance densities of decomposer organisms and processes, and rates of nutrient supply from the soil, as has been shown for invasion of Tradescantia fluminensis into forest understories in New Zealand (Standish et al 2004). Conversely negative belowground effects of invasive plants are also common, and a recent meta-analysis showed a weak overall negative effect of invasive plants on soil detritivores in forests (McCary et al 2016). As such, members of the Northern Hemisphere Pinaceae, which are invasive in many Southern Hemisphere ecosystems (Fig.…”
Section: Invasive Plantsmentioning
confidence: 99%